Aplicação da química quântica computacional no estudo de processos químicos envolvidos em espectrometria de massas Application of computational quantum chemistry to chemical processes involved in mass spectrometry - Ricardo Vessecchi; Sérgio E. Galembeck; Norberto P. Lopes; Paulo G. B. D. Nascimento; Antônio E. M. Crotti (Química Nova, 2008)
The field of application of mass spectrometry (MS) has increased considerably due to the development of ionization techniques. Other factors that have stimulated the use of MS are the tandem mass spectrometry (MS/MS) and sequential mass spectrometry (MSn) techniques. However, the interpretation of the MS/MS and MSn data may lead to speculative conclusions. Thus, various quantum chemical methods have been applied for obtaining high quality thermochemical data in gas phase. In this review, we show some applications of computational quantum chemistry to understand the formation and fragmentation of gaseous ions of organic compounds in a MS analysis.